The Christo-Centrism of Faith in Christ: Martin Luther's Reading of Galatians 2.16, 19–20 - Linebaugh, Jonathan A. (2013)
It is regularly suggested that the great weakness of reformational orderings of ‘faith’ and ‘justification’ is that they fail to coordinate Christology and the doctrine of justification. Behind this assertion is a particular construal of the pistis Christou debate: the interpretative decision to read Christ as the object of faith contributes to an anthropocentric account of justification whereas a ‘subjective’ interpretative of the genitive phrase restores the (Pauline) relationship between Jesus and justification. This article will argue that this is a misreading of Protestant theology, at least as it comes to expression in Martin Luther's exegesis of Galatians 2.16, 19-20 which presents a radically Christocentric account of ‘faith in Christ’. For Luther, the sola fide, as an interpretation of a Pauline antithesis—‘not by works of the law, but through faith in Jesus Christ’—, is an anthropological negation and a christological confession: it excludes the human as the subject of salvation and confesses Christ, who is present in faith, as the one by, in, and on the basis of whom God justifies the ungodly.
Keywords: Galatians; Faith; Pistis Christou; Martin Luther; Justification